Anti-tumor necrosis factor-a for the treatment of steroid-refractory acute graft-versus-host disease - Nogueira,M.C. (2007)
Allogeneic stem cell transplantation has been increasingly performed for a variety of hematologic diseases. Clinically significant acute graft-versus-host disease (GVHD) occurs in 9 to 50% of patients who receive allogeneic grafts, resulting in high morbidity and mortality. There is no standard therapy for patients with acute GVHD who do not respond to steroids. Studies have shown a possible benefit of anti-TNF-a (infliximab)for the treatment of acute GVHD. We report here on the outcomes of 10 recipients of related or unrelated stem cell transplants who received 10 mg/kg infliximab, iv, once weekly for a median of 3.5 doses (range: 1-6) for the treatment of severe acute GVHD and who were not responsive to standard therapy. All patients had acute GVHD grades II to IV (II = 2, III = 3, IV = 5). Overall, 9 patients responded and 1 patient had progressive disease. Among the responders, 3 had complete responses and 6 partial responses. All patients with cutaneous or gastrointestinal involvement responded, while only 2 of 6 patients with liver disease showed any response. None of the 10 patients had any kind of immediate toxicity. Four patients died, all of them with sepsis. Six patients are still alive after a median follow-up time of 544 days (92-600) after transplantation. Considering the severity of the cases and the bad prognosis associated with advanced acute GVHD, we find our results encouraging. Anti-TNF-a seems to be a useful agent for the treatment of acute GVHD.